THE EMOTIONAL LANDSCAPE OF MURRAY BAIL’S EUCALYPTUS: DESIRE, ATTACHMENT, AND ISOLATION - Eshankulova Lola Sayfullayevna; Muxammedova Nafisa Kamolovna (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
This article examines how Murray Bail’s Eucalyptus (1998) constructs an “emotional landscape” through three interlocking dynamics: desire, attachment-as-control, and isolation. The novel’s central premise—Holland offering his daughter Ellen in marriage to any suitor who can name every eucalyptus on his property—operates as more than a quirky plot device. It stages a politics of feeling in which desire is routed through classification and possession, attachment is enacted as surveillance and containment, and isolation emerges as both spatial enclosure and affective deprivation. Methodologically, the study uses close reading, thematic coding, and narratological analysis of recurring devices (taxonomic listing, the gaze, fairy-tale framing, and storytelling as seduction). The discussion synthesizes key scholarship on Eucalyptus that reads the novel through ecofeminist critique, cultural-symbolic accounts of the eucalypt, legal/postcolonial reflections on naming, and critical plant studies. Findings suggest that the novel’s emotional economy is driven by a “logic of domination” in which naming and owning become affective practices-organizing characters’ longing, dependence, and estrangement-while the text’s parodic mode both exposes and, at times, risks reproducing gendered and colonial patterns.